COVID-19 Marked a Change in the Scope of Occupational Medicine from Occupational to Work-Related Diseases and Total Worker Health® - Corradi, Massimo; Ranzieri, Silvia (La Medicina del Lavoro, 2023)
The COVID-19 pandemic challenged occupational medicine, while its focus had already shifted from occupational diseases to work-related illnesses. Such a broader scope allowed the inclusion of transmissible diseases among the causes for concern in working settings. COVID-19 has had a profound impact globally, resulting in millions of infections, often lethal. From its appearance, COVID-19 was found to affect specific groups of workers at higher risk of contracting the virus due to their occupation or workplace conditions, which accounts for its consideration as a potential work-related disease. This overview examines various aspects of COVID-19 based on articles published in our journal. Specifically, the epidemiology of COVID-19 is discussed, including mortality rates and groups at higher risk. The diagnosis, measures to prevent contagion, vaccination efforts, long-term effects, and psychosocial factors are also summarized. The emerging picture is that COVID-19 has been a trigger accelerating the change of paradigm of occupational medicine, which is more and more concerned with prevention. Occupational Health contributes to health promotion and Total Worker Health®.